A Decision Support System of Scholarship Grantee Selection Using Moora - Rodhiyah Mardhiyyah; Rr. Hajar Puji Sejati; Devi Ratnasari (Association for Scientific Computing Electrical and Engineering, 2019)
Scholarships are awards from an institution or an individual to someone for educational purposes. Scholarships can be given free or on conditions that prospective scholarship grantee must-have. The scholarship grantee selection process is usually with several criteria in order to get grantee who can be declared elected as scholarship grantee. The use of several criteria in the selection process requires more analysis to determine the scholarship grantee. Moora (Multi-Objective Optimization on The Base of Ratio Analysis) is one of the methods of decision support systems that can be used to assist decision-makers in making decisions. This study takes scholarship acceptance criteria as a parameter then each parameter is given a weight based on the priority of each parameter. The results of this study are to get an optimization value of each alternative then after ranking, it can be seen the ranking of scholarship grantee.